A STUDY ON CORPORATE ENTREPRENEURSHIP DEVELOPMENT THROUGH ORGANIZATIONAL LEARNING ABILITY AND JOB SATISFACTION - SHRAVANI, B.; MAHESH, K. (International Journal of Psychosocial Rehabilitation, 2021)
The purpose of this article is to look into the relationship between corporate entrepreneurship and organizational learning capability. The data was collected using a survey method from 250 middle-level managers in the chemical engineering manufacturing industries. The Organizational Learning Capability (OLC) measurement instrument, which consists of 14 items divided into 5 dimensions: experimentation, risk taking, engagement with the external environment, discussion, and participative decision-making, was used to assess corporate entrepreneurship. The findings of this study show that organizational learning capability and corporate entrepreneurship have a positive relationship.